MITIGATING ADOLESCENT POST-TRAUMATIC STRESS DISORDER THROUGH INDIVIDUAL COUNSELING USING EYE MOVEMENT DESENSITIZATION REPROCESSING TECHNIQUES: A STUDY ON SURVIVORS OF TRAIN ACCIDENTS - Wahid, Ahmad; Nirwana, Herman; Hariko, Rezki; Fikri, Miftahul; Choiri, M. Fadlan; Putri, Kanaya Yose; Fazria, Nurul (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Diverse individual experiences and problems often lead to painful psychological disorders, one of which is the traumatic experience of individuals who have been involved in train accidents, which can lead to post-traumatic stress disorder. This condition requires responsive and serious attention, as it can have negative and long-lasting effects. One effort that can be made to overcome this problem is the implementation of individual counseling using the eye movement desensitization reprocessing technique. This study focused on empirically testing the effectiveness of individual counseling using the eye movement desensitization reprocessing technique in reducing PTSD in adolescents who have experienced train accidents. The research method used was an experiment with a single subject research design. The sample in this study consisted of two students who had experienced a train accident and had high levels of PTSD. The results showed that individual counseling using the eye movement desensitization reprocessing technique was effective in reducing PTSD in adolescents who had experienced a train accident. Visual analysis shows a consistent and significant decline in clients. Both clients who were initially identified as having PTSD no longer showed signs of PTSD after undergoing 3 and 4 sessions of intervention. However, the findings of this study should not be generalized to samples with different characteristics. The researchers recommend that future researchers apply individual counseling using eye movement desensitization reprocessing techniques to populations and samples with broader characteristics, as well as other relevant issues.